Islamic State and Southern Philippines : Teneous links with militants - Joseph, Franco (2014)
The Islamic State(IS) has aroused much media attention in the Philipines, with concerns raised over pledges of allegiance(bay'at) made by leaders of two groups of Muslim militants. However, links remain normative rather than operational, given the dissonance between IS ideology and Mindanao rebels.